The legal basis for the right to compensation for eviction in Moroccan commercial leases - GASMI Imane; Menouane Azzab (International Journal of Scientific Research and Innovative Studies, 2025)
Eviction compensation, at the heart of the Moroccan commercial lease legal system, is one of the most emblematic mechanisms for reconciling property rights and economic stability. Established by Law 49-16, it enshrines a genuine subjective right for tenants, based on respect for contractual good faith and the legitimacy of the grounds for eviction. The study highlights the dual nature of this institution: legal and economic. From a legal standpoint, eviction compensation is based on law and case law, which have made it an autonomous property right, detached from the simple contractual relationship. From an economic standpoint, it fulfils a regulatory and corrective function, aimed at preventing property speculation, protecting the value of business assets and promoting fairness in rental relationships. Through an analysis of recent decisions by Moroccan commercial courts, this article demonstrates that eviction compensation goes beyond the logic of compensation to become an instrument of contractual justice and moralization of the rental market. Today, it embodies a form of economic justice, where civil law is open to considerations of stability, fairness and mutual trust between commercial actors. Keywords: Commercial lease – Eviction compensation – Good faith – Contractual justice – Business assets – Economic regulation – Moroccan case law. Received Date: October 20, 2025 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/570